Indicaciones Geográficas en Argentina: aportes metodológicos para el estudio de sus potencialidades y limitantes - Cendon, Maria Laura (2018)
The Geographical Indications (GI) are signs of territorial quality that may contribute to producers organization, the introduction of innovations and the valuing of differential quality. In this sense, the GIs are regarded as tools that enhance territorial development due to the comprehensive valorization of the local resources. In Argentina, the studies on differential quality labels have been undertaken only recently, which means that there are not many bibliographical sources on these processes or their multiple effects. The objective of this study is to systematize and understand the implementation of the Designation of Origin and Geographical Indication processes in Argentina, and to provide methodological contributions to study the potential benefits of these tools to the territorial development. The references adopted in this study were the LAFS approach and the notion of territorial development. The latter is considered a process of productive, institutional and social transformation. Qualitative methodology based on the review of primary and secondary sources on the eight GIs from Argentina was adopted. The results show the complexity of the collective qualification processes that result in productive transformations, as well as the development and strengthening of public-private and interinstitutional networks for both the creation of the quality protocol and promotion and dissemination of the product. Similarly, the role of local institutions and governments in the accompaniment, consultancy and organization of these activities is highlighted. These actions conduce to the rise of the heritage status of local food culture and collective identity.